Sustainable Village Fund Allocation for Indigenous Communities: A Culturally Responsive Analysis of the Baduy of Indonesia - Sumantri, Joko (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the misalignment between Indonesia’s standardized Village Fund allocation system and the socio-cultural realities of indigenous communities, highlighting the need for Indigenous Budgeting Systems that better reflect customary governance structures and local priorities. Drawing on participatory budgeting theory, indigenous governance frameworks, and SDG Localization, the study critiques the limitations of uniform fiscal accountability mechanisms and develops a budgeting approach grounded in Local Wisdom-Based Development. The research employs qualitative fieldwork, including in-depth interviews with Baduy leaders, government officials, and financial managers, complemented by document analysis and thematic mapping. A weighted relevance scoring system is used to assess the alignment between all 17 SDGs and both the existing and proposed budgeting models. Findings indicate that the Baduy community rejects the current arrangement due to administrative burdens, documentation requirements, and infrastructure-oriented spending that conflict with customary norms. SDG 1, SDG 2, SDG 13, SDG 15, and SDG 16 emerge as the most relevant to Baduy development priorities. The proposed framework supports Village Fund Reform by emphasizing direct cash assistance, agricultural land expansion, and simplified accountability mechanisms aligned with oral traditions and customary law. The study situates its contribution within ongoing scholarly debates on indigenous public finance and SDG implementation, drawing on qualitative insights from the Baduy case to inform the design of more culturally responsive and context-sensitive budgeting reforms.